Approaches for prevention and management of menstrual bleeding in adolescent patients undergoing cancer treatment - L. V. Adamyan; E. V. Sibirskaya; L. G. Pivazyan; S. G. Isaeva; S. L. Barsegyan; E. A. Zarova (Опухоли женской репродуктивной системы, 2025)
Abnormal uterine bleeding (AUB) is bleeding that is excessive in frequency, duration and/or volume of blood loss compared to normal menstruation. AUB is one of the most common gynecological problems and occurs in 3–30 % of women of reproductive age. Adolescent patients undergoing cancer treatment are at high risk of presenting AUB associated with thrombocytopenia, coagulopathies, dysfunctions of hypothalamic-pituitary-gonadal axis. According to the National Institution of Oncology up to 5 % of new cancer cases are diagnosed in women aged from 15 to 39 years, which underlines the relevance of the problem. AUB is a serious complication that can result in anemia and lifethreatening bleeding. Thus, even normal menstrual blood loss can cause adverse outcomes in women who already suffer from anemia and/or thrombocytopenia. To prevent severe uterine bleeding during the treatment of oncology oncologist, obstetrician-gynecologist and a hematologist are required. Causes of AUB, management approaches and prevention therapy for oncological patients are considered in this article.